Remotion of Hydrogen Sulfide in Absorption Column - Porto, F. G. M; Begnini, M. L; Finzer, e J. R. D (Journal of Food Technology Research, 2017)
Some physical, chemical or electrochemical phenomena that cause the decomposition of a material, usually metallic, they can be defined as corrosion. Analyzing the adverse means and determining its characteristics, several efficient methods can be developed to prevent it, consisting in one of them the absorption of the oxidizing agent. This technique is based on significantly reduce the concentration of the compound. As the hydrogen sulfide corrosive substance, its excessive presence in gas streams intensifies the deterioration of equipment during the contact. The objective was to absorb hydrogen sulfide from biogas. The absorption study was conducted by applying a 5% sodium hydroxide solution. The device designed consisted of a cylindrical packing column, bearing a gas inlet and a distributor at the bottom, which further supports the packing, and a liquid inlet and distributor at the top. The treated gas is released from the top of the column, and the liquid is discharged at the bottom, containing hydrogen sulfide absorbed in the form of salts. In the design, the biogas flow was 15m³/h with 3% mole hydrogen sulfide and the tower was package with Rasching rings of 1.5 inches. The calculations performed have enabled the design of an absorption column 0.10 m in diameter and 3.00 m height of the packing, causing a loss in pressure of 0.5 cm water/m column.